Treatment of Severe Unconjugated Hyperbilirubinemia with Phenobarbitone in Two First-Degree Siblings with Crigler-Najjar Syndrome (CNS) Type 2: A Success Story - Kumar, Sachin; Karthik, Siddhavatam Rahul; Pahuja, Gandharav; Chakrabarti, Sarthak; Panda, Prateek Kumar; Sharawat, Indar Kumar (Archives of Pediatric Gastroenterology, Hepatology, and Nutrition, 2025)
Background: Crigler–Najjar syndrome (CNS) type 2 is a rare autosomal recessive disorder of bilirubin conjugation caused by mutations in the UGT1A1 gene. It presents in infancy with unconjugated hyperbilirubinemia that does not respond to phototherapy but improves with phenobarbitone, which enhances residual enzyme activity. Although phenobarbitone remains the cornerstone of treatment, familial recurrence of CNS type 2 is rarely reported in pediatric literature. Case: We report two siblings born to consanguineous parents who presented with progressive jaundice during early infancy. The first child, a 2-month-old boy, had multiple hospitalisations for phototherapy without benefit. Laboratory evaluation revealed total bilirubin of 31 mg/dL with normal liver function and no evidence of hemolysis. Genetic testing confirmed a homozygous UGT1A1 (c.1456T>G; p.Tyr486Asp) mutation. He was treated with phenobarbitone (5–8 mg/kg/day) and calcium phosphate, achieving a bilirubin level <10 mg/dL within 4 weeks. Three years later, his younger sister developed similar unconjugated jaundice from day 4 of life and harboured the same mutation; she responded well to phenobarbitone alone. Both siblings remain well on long-term follow-up. Discussion: This case highlights the genetic basis and favorable response of CNS type 2 to phenobarbitone, which induces hepatic UGT1A1 expression. Familial clustering of CNS 2, though reported in few global studies, is seldom documented from India. Conclusion: Early genetic diagnosis, timely institution of phenobarbitone, and family counselling are critical for successful management of CNS type 2. These cases reaffirm the long-term safety and efficacy of phenobarbitone in familial presentations of this rare disorder.